2010
DOI: 10.3727/096368910x503415
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Host Blood Factors and Brain Glia Accompanying the Functional Recovery after Systemic Administration of Bone Marrow Stem Cells in Ischemic Stroke Rats

Abstract: In this study, we examined the effects of systemic administration of rat or human bone marrow stromal stem cells (MSC) at early and later times following middle cerebral artery occlusion (MCAO) on blood cytokines/ growth factors, brain glia, and motor behavior in rats. Rats were tail vein injected with rat (r) and human (h) MSCs at 1 or 7 days post-MCAO. In some rats (N = 4) MSCs isolated from transgenic GFP rats were used to track the migration of cells peripherally and centrally at 2.5 and 28 days. Motor beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 62 publications
4
87
0
Order By: Relevance
“…24 This, in turn, may be mediated by the outgrowth of nerve fibers of endogenous neurons. 23,25 Other studies have demonstrated that stem cell therapy results in the upregulation of growth factors that may be responsible for the outgrowth of these endogenous fiber processes 26 and for the inhibition of inflammatory processes, 27 which may lead to secondary cell loss within the brain. These observations offer intriguing alternative mechanisms that may underlie the restorative effects noted with stem cell therapy following stroke and provide a rationale basis for clinical trials.…”
Section: Mechanisms Of Action Of Stem Cells In Ischemic Strokementioning
confidence: 99%
“…24 This, in turn, may be mediated by the outgrowth of nerve fibers of endogenous neurons. 23,25 Other studies have demonstrated that stem cell therapy results in the upregulation of growth factors that may be responsible for the outgrowth of these endogenous fiber processes 26 and for the inhibition of inflammatory processes, 27 which may lead to secondary cell loss within the brain. These observations offer intriguing alternative mechanisms that may underlie the restorative effects noted with stem cell therapy following stroke and provide a rationale basis for clinical trials.…”
Section: Mechanisms Of Action Of Stem Cells In Ischemic Strokementioning
confidence: 99%
“…A major component of regenerative medicine is stem cell-based therapeutics, which have shown promising therapeutic potential for various types of neurological disorders, including TBI (e.g., 57,58,62,109,130), and have reached limited clinical trials [for review see (43)]. Translating cell therapy for treatment of brain diseases to the clinic has involved testing the safety, efficacy, and mechanisms of action of a variety of transplantable donor cells, including fetal stem cells, cancer-derived neuron-like cells, embryonic stem cells, induced pluripotent stem cells, and adult stem cells, such as umbilical cord blood, bone marrow stromal cells, amnion cells, among others (16,57,58,62,63,74,75,84,87,90,109,130). However, among these various types of stem cells, adult stem cells are of interest, as they circumvent ethical and moral problems and also teratogenic and oncogenic risks usually associated with transplantation of embryonal or fetal-derived stem cells (85).…”
Section: Stem Cell Transplantation In Tbimentioning
confidence: 99%
“…Most studies have administered cells early (6-48 h) or at subacute phase (2-7 days) after stroke and only few comparisons have been made. Omori et al (2008) compared multiple time points and found that the greatest functional benefit was achieved when BM-MSCs were injected 6 h after stroke compared to later time points, which is supported by the finding of Yang et al (2010) that cells delivered 1 day have greater effect than those at 7 days. Instead, Mays et al (2010) reported time window from 1 to 7 days post-stroke to be equally beneficial.…”
Section: Adult Stem/progenitor Cellsmentioning
confidence: 51%
“…When considering studies using human cells, mostly bone marrow stem/stromal cells (BM-MSC) (Li et al, 2002;Zhao et al, 2002;Chen et al, 2003;Zhang et al, 2004;Omori et al, 2008;Andrews et al, 2008;Mays et al, 2010;Yang et al, 2010;Bao et al, 2011) or UCBCs (Chen et al, 2001;Willing et al, 2003a;Borlongan et al, 2004;Vendrame et al, 2004;Xiao et al, 2005;Newcomb et al, 2006;Chen et al, 2006;Mäkinen et al, 2006;Zhang et al, 2011;Riegelsberger et al, 2011) have been used. Most studies have administered cells early (6-48 h) or at subacute phase (2-7 days) after stroke and only few comparisons have been made.…”
Section: Adult Stem/progenitor Cellsmentioning
confidence: 99%